"We Shall Overcome" A Humanity Song by Roger Waters: Critical Discourse Analysis - Inike Tesiana Putri; Sulis Triyono (Humaniora, 2018)
Language is an essential feature of communication for all poeple. It is utilized through various tools and media, and singing songs is one of the traditional forms of communication. Songs are usually written for particular reasons, messages, and purposes, and sometimes targeted for specific audience or listeners. Song lyrics usually contain various themes such as social and current issues and problems which the songwriter strives to share through expressions of his or her ideology, thoughts and feelings. This paper is aimed to find out the text analysis, social cognition and social context in the humanity song entitled We Shall Overcome through Teun A. van Dijk’s Critical Discourse Analysis model. This model shows that the choice of words or the diction is cohesive and coherent and is able to communicate the general meaning of this humanity song. Furthermore, the social cognition in this humanity song is related with the current social context which involves the recent situation in Palestinine, where there is still in conflict with Israel.